Honor thyself - Steel, Danielle (Delacorte Press, 2008)
A legend of film and stage, Carole Barber goes to Paris to work on her novel and ends up in the hospital after a traffic accident. In the days that follow, the paparazzi swarm. A mysterious stranger, a man famous in his own realm, quietly visits the hospital to see the woman he once loved and never forgot. Carole's two grown children rush to her bedside. She awakens to a second chance to count her blessings, heal wounded hearts, recapture lost love.